Novel Tissue Harmonic Imaging Clearly Visualizes a Case of Intraductal Papillary Mucinous Neoplasm with Mural Nodules - Matsumoto, Kazuyuki; Katanuma, Akio (JOP. Journal of the Pancreas, 2014)
Tissue Harmonic Echo (THE) imaging is a sonographic technique that potentially provides images of higher quality than can conventional B-mode images. Potential advantages of THE imaging include improved resolution, improved signal-to-noise ratio, and reduced artifacts [1, 2]. Recently, a novel THE imaging performed using an EUS system with a monitor/processing unit (EU-ME2 PREMIER PLUS; Olympus Medical Systems, Tokyo, Japan) has been developed. Using this technology, we can obtain two THE mode images, namely, THE-P (penetration) and THE-R (resolution). The THE-P mode is suitable for middle range distance observation because it receives a harmonic signal whose frequency is mainly 7.5 MHz. The THE-R mode is suitable for close distance observation from the probe because it receives a harmonic signal whose frequency mainly ranges from 10 to 12 MHz. Here, we report a case of intraductal papillary mucinous neoplasm (IPMN) with mural nodules which could be clearly detected using this novel THE imaging. Image: P-mode image.